Pengaruh Gaya Kepemimpinan Demokratis Kepala Sekolah terhadap Kedisiplinan Guru - Alam, Rofiqoh Nurul; Supendi, Pepen (Jurnal Tinta, 2025)
Teacher discipline plays an important role in creating effective learning while reflecting professionalism and being a role model for students. However, there are still teachers who lack discipline, so the role of the principal is needed through the implementation of appropriate leadership. This study aims to analyze the democratic leadership style of the principal, teacher discipline, and the influence of both at Triyasa Junior High School, Bandung City. This research method uses a quantitative approach with a survey method through questionnaires and documentation studies. The results show that the democratic leadership style of the principal is in the high category with an average value of 4.00, while teacher discipline is also high with an average value of 4.22. The influence of democratic leadership style on teacher discipline is 45.5% based on the coefficient of determination (R2 = 0.455), while 54.5% is influenced by other factors. Thus, democratic leadership style has a positive and significant effect on teacher discipline. Principals are recommended to maintain a democratic leadership style while still emphasizing firmness in imposing sanctions.